Stunting Prevention from Upstream to Downstream by Empowering Adolescents through GEMASAZIPRO (Youth Movement for Nutrition and Reproductive Health): Pencegahan Stunting dari Hulu ke Hilir dengan Memberdayakan Remaja melalui GEMASAZIPRO (Gerakan Remaja Sadar Gizi dan Kesehatan Reproduksi) - Sulikah; Nurlailis Saadah; Budi Joko Santosa; Uswatun Khasanah (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Marriages conducted during adolescence generally cause physiological, psychological, and socioeconomic problems. These problems include abortion due to an immature uterus or the mother's unpreparedness to care for a child, which can lead to stunting in children. Activities carried out in this community service include disseminating material on reproductive health and sex education, motivating adolescents to avoid early marriage, and fostering harmonious relationships between adolescents and their parents. This community service activity also provides training and mentoring for adolescents and increases their understanding and knowledge of reproductive health, sex education, and stunting prevention. This community service utilizes a combination of several models, including village community participation, community development, persuasiveness, and education. The results of the activities are an increase in adolescent knowledge and understanding of reproductive health, sex education and its impact, the importance of nutrition, and reproductive health. Adolescents are motivated and have a commitment and enthusiasm to graduate from school, harmonious relationships are established between adolescents and their parents, and a youth study group is formed, organized regularly by the mosque youth every month. The results of the activities also show the implementation of beneficial activities for adolescents, and the implementation of monthly youth integrated health posts (Posyandu) by youth cadres.